Хозяйственно-биологическая оценка разных видов эспарцета на юге России - S. A. Ignatiev; T. V. Gryazeva; N. G. Ignatieva (Зерновое хозяйство России)
Economic and biological estimation of various species of sainfoin in the south of Russia Thirty three samples of three sainfoin species ( Onobrychis viciifolia, Onobrychis montana, Onobrychis arenaria and hybrid of the local breeding ) were studied in the collection seed plot in 2014. The soil of the plot was blackearth (chernozem obyknovenny). During the vegetation meteorological conditions were characterized by the insufficient humidity with high dayly temperatures. The study determined that there were no differences in the phenological phases between samples of sainfoin and the standard variety ‘Zernogradsky’. The length of the period from spring sprouting till flowering was 58-59 days, till seed maturity was 94-95 days. The standard variety surpasses such samples of the local breeding as ‘S 3/05’, ‘Sin 12’ and ‘GIA 2’ in plant height. The samples of the sainfoin Onobrychis viciifolia ‘к-42089’, ‘к-29014’ and the local breeding material ‘S 4/05’, ‘Sin’ 12, ‘GIA 2’, ‘GIA 5’ showed more than 50% of leaf amount. Only the samples of the local breeding ‘S 2/05’, ‘S 4/05’, ‘S 6/05’, ‘Sin 12’, ‘GIA 1’ produced the largest amount of green chop compared with the standard variety ‘Zernogradsky 2’. 33% of samples surpassed the standard variety in seed productivity. The largest amount has been produced by the following samples: ‘к-29014’ (340.5 g/m2), ‘к-47782’ (308.0 g/m2), ‘к-32788’ (303.0 g/m2), ‘к-26770’ (300.0 g/m2), ‘Sin 12’ (300.0 g/m2), ‘GIA 5’ (305.5 g/m2), ‘С 3/05’ (320.5 g/m2) and ‘GIA 2’ (345.0 g/m2). The content of raw protein in the samples of collection ranged from 15.59% to 19.99% that testifies the possibility of sainfoin breeding for its increased content of dry matter. There are 60% of samples in the collection with 18% of raw protein, and more than 27% of samples have more than 19% of raw protein. The samples ‘к-28630’, ‘к-29084’, ‘к-29014’, ‘S 2/05’, ‘S 3/05’, ‘S 4/05’, ‘Sin 12’, ‘GIA 5’ and ‘GIA 11’ are of the greatest interest for breeding of qualitative sainfoin. A number of the studied samples having a set of economic-valuable traits are going to be used in the future breeding work.